2020
DOI: 10.18632/oncotarget.27680
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial uncoupling and the disruption of the metabolic network in hepatocellular carcinoma

Abstract: Background: Hepatocellular Carcinoma (HCC) is the third most common cause of cancer related death worldwide. Adequate treatment options for patients with advanced HCC are currently limited. Materials and Methods: We studied the anti-HCC effect of FH535 and a novel derivative Y3, on proliferation, mitochondrial function and cellular metabolism focusing on the three key substrates, glutamine, glucose, and fatty acids. Results: FH535 and Y3 disrupted mitochondrial redox control in HCC cells that resulted from unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The association between high Treg infiltration and poorly differentiated HCC in primary tumor samples, together with the potent anti-HCC activity of NEBs 9 , 11 , 14 , 15 led us to interrogate the immunoregulatory effects of FH535 in primary human Treg and Tconv.…”
Section: Resultsmentioning
confidence: 99%
“…The association between high Treg infiltration and poorly differentiated HCC in primary tumor samples, together with the potent anti-HCC activity of NEBs 9 , 11 , 14 , 15 led us to interrogate the immunoregulatory effects of FH535 in primary human Treg and Tconv.…”
Section: Resultsmentioning
confidence: 99%
“…These observations support that mitochondrial OXPHOS is still present and active in tumor cells and highlight the notion that tumor cells are highly heterogeneous in terms of metabolic pathways [9,22,[38][39][40][41][42][43][44][45]. The existence of an active mitochondrial metabolic network, specifically TCA cycle and ATP synthesis through the OXPHOS machinery has actually been demonstrated in different types of cancer cells to support the high demand on biomolecules, as building blocks for macromolecules, and energy for their proliferation and conversion to a metastatic phenotype (i.e., epithelial-to-mesenchimal transition) [12,27,37,44,[46][47][48][49][50][51][52][53][54][55]. We recently showed that, in melanoma cells, a functional OXPHOS machinery is strictly associated with mitochondrial Ca 2+ and ROS homeostasis while a perturbation of the mitochondrial metabolic functions (decreased oxygen uptake, reduced expression of OXPHOS proteins and ATP production), together with a disruption of the Ca 2+ /ROS homeostasis, triggers both canonical (apoptosis) and non-canonical (paraptosis) death mechanisms, thus regulating the cell survival/death balance [56,57].…”
Section: Metabolic Rewiringmentioning
confidence: 96%
“…Specifically, they highlighted that sorafenib, dasatinib and regorafenib induce cancer cell death and antitumoral autophagy, by triggering mitochondrial dysfunction through the inhibition of the ETC complexes, AMPK activation and mTOR inhibition, and a dysregulation of the mitochondrial Ca 2+ and ROS homeostasis [319]. Sorafenib was also demonstrated to act synergystically with FH535 (an inhibitor of the Wnt/β-catenin pathway) in inducing hepatocellular carcinoma cell death by dysrupting cell bioenergetics and mitochondrial functions [54,320].…”
Section: Targeting Mitochondrial Functional and Structural Dynamicsmentioning
confidence: 99%
“…The overexpression of the ubiqinol-cytochrome C reductase hinge protein (UQCRH), a component of the respiration complex, is frequently found in advanced HCC tissues [102]. The interplay between the Wnt/β-catenin pathway and mitochondrial activity has been found to regulate the metabolic network in HCC cells [103]. Wnt/β-catenin inhibitors, including FH535 and Y3, impair mitochondrial OXPHOS and disrupt transmembrane potential and the electron transport chain, thereby reducing ATP production and inhibiting the proliferation of Huh7, Hep3B, and PLC/PRF/5 cells.…”
Section: Hcc and Shifted Mitochondrial Metabolismmentioning
confidence: 99%